Analisis Tingkat Keterbacaan Buku Teks Bahasa Indonesia Kelas V Madrasah Ibtidaiyah Al-Zaytun - Ita Rosita; Anjar Sulistyani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Textbooks have an important role and function as teaching materials. So, the content of discourse in textbooks should not make it difficult for students to understand and reason. The presence of textbooks with various authors and publishers, sometimes not in accordance with their roles and functions, especially Indonesian textbooks published by Erlangga are still considered difficult by students. This study aims to determine the level of student readability of Indonesian textbooks published by Erlangga with the book title ESPS (Erlangga Straight Point Series) Indonesian class V SD/MI 2013. This study uses a qualitative approach by conducting direct observations in the field. The population in this study is the subject of the Indonesian Language ESPS textbook for SD/MI Class V published by Erlangga, class V MI Al-Zaytun students totaling 239 students, while the sample taken is 30 students. Data was collected by observing, giving gaps in text, and calculating the percentage using the Kloz test technique. Data analysis was carried out by determining the assessment criteria using the Kloz test, namely calculating the test score by multiplying the number of correct entries by 100 divided by the number of gaps. If the percentage gain is above 60%, then the discourse is classified as